The effectiveness of support group and pedometer in increasing physical activity in sedentary adults in Kota Bharu Kelantan - Abdullah, Nur Emillia (2015)
Introduction: Sedentary lifestyle is a risk for diabetes, hypertension, cardiovascular disease and obesity. This trial assessed the effect of support group and pedometer among sedentary adults in Kota Bharu, Kelantan. Objectives: To determine the effectiveness of support group and pedometer in increasing physical activity of sedentary adults. To determine the effectiveness of support group intervention in increasing step counts, energy expenditure and on cardiovascular health outcome such as blood pressure, weight, body mass index, waist circumference and blood profiles. Methods: This was a randomized controlled trial of 80 patient randomly allocated to either support group or control group. At baseline and after 3 months after the intervention, steps counts, total daily energy expenditure and cardiovascular health outcome parameters were assessed. Results: The steps counts at month 2 and month 3 of intervention were significantly improved for support group intervention. The parameter of weight and BMI showed significant changes after 3 months intervention for the support group. Conclusion: This study showed promising result for support group intervention together with pedometer in increasing physical activity among sedentary adults.